1992
DOI: 10.1007/bf00960776
|View full text |Cite
|
Sign up to set email alerts
|

Prospective versus retrospective assessment of Menstrual cycle symptoms and moods: Role of Attitudes and beliefs

Abstract: Prospective vs. retrospective self-reports of menstrual cycle symptoms and moods in users and nonusers of oral contraceptives were investigated. Subjects, aged from 17 to 27 years, included 56 women on the pill and 47 nonusers. The Menstrual Distress Questionnaire (MDQ) quantified physical symptomatology, while the Differential Emotions Scale (DES-IV) measured emotional states. Prospective reports suggested less discernible symptom and mood effects than did retrospective reports. Physical symptoms were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Study 1 asked women for retrospective reports of changes experienced during their pregnancy but there is evidence to suggest that retrospective measures may not always produce the same results as prospective measures (e.g. Boyle and Grant, 1992;Yu et al, 1996), and that the latter might be more reliable (e.g. Taffe and Dennerstein, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Study 1 asked women for retrospective reports of changes experienced during their pregnancy but there is evidence to suggest that retrospective measures may not always produce the same results as prospective measures (e.g. Boyle and Grant, 1992;Yu et al, 1996), and that the latter might be more reliable (e.g. Taffe and Dennerstein, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There are several methodological problems associated with their study, as it was correlational, and retrospective. Numerous studies have found that retrospective reporting of menstrual cycle symptoms results in an exaggeration of responses compared with prospective reporting [9,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Since the 'trait' version of the MDQ (Form C) was administered, the particular menstrual-cycle phase each student was in on the day of testing was irrelevant, as retrospective reports were obtained from each student (cf. Boyle & Grant, 1992;Grant & Boyle, 1991). Since virtually all students invited to participate in the study did so, the sample probably remained representative of adolescent female students.…”
Section: Samples and Proceduresmentioning
confidence: 99%
“…Complaints of adverse menstrual-cycle effects on school grades may derive partially from societal beliefs and expectations (e.g., Boyle & Grant, 1992;Endicott & Halbreich, 1982;Grant & Boyle, 1991;Richardson, 1991), combined with the observation that females more readily admit to negative moodstates (Boyle, 1985a).…”
mentioning
confidence: 99%
See 1 more Smart Citation